Long-term antibody response after Covid-19 vaccination in health care workers- a single centre study from Pakistan - Kanani, Fatima; Aijaz, Javeria; Anis, Sabiha; Mushtaq, Mamoona (Journal of the Pakistan Medical Association, 2025)
The retrospective cohort study was planned to determine long-term anti-spike immunoglobulin G levels after receiving coronavirus disease-2019 vaccination by healthcare workers. The study took place between June and July 2022 at the Indus hospital in Karachi. Healthcare workers who had previously screened negative to pre-vaccination Severe Acute Respiratory Syndrome Coronavirus 2 nucleocapsid antibodies were tested for post-vaccination Severe Acute Respiratory Syndrome Coronavirus 2 anti-spike immunoglobulin G levels using a quantitative assay. The test was also performed on the stored pre-vaccination samples of the subjects collected up to 18 months previously. Antibody levels in subjects without infection, with infection and with booster administration were compared. The median post-vaccination anti-spike immunoglobulin G in infected only, infected with routine vaccination and infected with booster values were 1,725.6 IU/mL (interquartile range: 684.80-4,708.9 IU/mL), 2,067.15 IU/mL (interquartile range: 705.33-4,670.4 IU/mL) and 6,139.15 IU/mL (interquartile range: 2,426.05-10,623.40 IU/mL). There was a doubling of antibody titers, from 1,744 IU/mL to 3,829 IU/mL, in those who received a booster versus routine vaccination (p>0.05). The antibodies remained positive more than a year following vaccination. Key Words: Healthcare workers, Anti-spike IgG, Sinopharm, CanSino-Biologics, Pfizer, Booster.